Phytochemical Profiles of Alpine Plant Horminum pyrenaicum L. during Phenological Growth Stages. Issue 10 (24th September 2018) - Raudone, Lina; Motiekaityte, Vida; Vainoriene, Rimanta; Zymone, Kristina; Marksa, Mindaugas; Janulis, Valdimaras
Abstract : Horminum pyrenaicum L. is a medicinal, aromatic and ornamental plant native to the Pyrenees and Alps. The phytochemical composition is affected by various ecological factors, climatic conditions and cultivating factors, and especially phenological growth stages. Flavonoids, phenolic acids and triterpenic acids were identified and quantified in the above‐ground parts of H .  pyrenaicum during the phenological stages. The massive flowering was distinguished with the greatest total amounts of phenolic compounds (22232.8 μg/g), and rosmarinic acid was the predominant compound. The amounts of triterpenic compounds were at the lowest during the intense growth stage and significantly increased up to the massive flowering. The prevailing compounds were ursolic acid and betulinic acid, 12092.4 μg/g and 2618.9 μg/g, respectively. The major essential oil compounds were β ‐phellandrene (56.6%), caryophyllene oxide (5.9%), ( Z )‐caryophyllene (4.4%), myrcene (4.1%) and thymol (3.6%). Selecting the optimal harvesting time could ensure the herbal raw material rich with preferred bioactive compounds. Abstract :